'We Know but We Don't Really Know': Diet, Physical Activity and Cardiovascular Disease Prevention Knowledge and Beliefs Among Underserved Pregnant Women. - Beckham, A.; Urrutia, Rachel; Sahadeo, Latoya; Corbie-Smith, Giselle; Nicholson, Wanda (Maternal & Child Health Journal, 2015)
To describe the knowledge of underserved pregnant women related to diet, physical activity, and cardiovascular disease (CVD). Underserved pregnant women from the University of North Carolina and Pitt County, North Carolina participated in 9 focus group interviews. Focus group questions focused on knowledge of CVD risk factors, lifestyle prevention strategies such as diet and physical activity, and the sources of such knowledge. Data were analyzed with the constant comparative method. Prior to the focus group, each woman was invited to complete a telephone survey to collect demographic information and responses to a 13-item CVD knowledge questionnaire. Means and frequency procedures were used to analyze demographic information. Fifty women participated in nine focus group interviews. Participants possessed basic knowledge of CVD risk factors and preventive strategies, such as basic guidelines and recommendations for healthy diet and physical activity in pregnancy. However, women often receive incomplete guidance from obstetric providers, and women, therefore, desired more information on these topics. Some gaps were filled by nurses and nutritionists. Women also sought information from female friends and relatives. Incorrect knowledge was demonstrated in all groups and led to less healthful behaviors in some cases. Underserved pregnant women have basic knowledge about healthy lifestyle and CVD prevention behaviors; however important gaps and misinformation exist.